2010
DOI: 10.1158/1078-0432.ccr-10-0987
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Thio-Trastuzumab-DM1 Conjugate with an Improved Therapeutic Index to Target Human Epidermal Growth Factor Receptor 2–Positive Breast Cancer

Abstract: Purpose: Antibody drug conjugates (ADCs) combine the ideal properties of both antibodies and cytotoxic drugs by targeting potent drugs to the antigen-expressing tumor cells, thereby enhancing their antitumor activity. Successful ADC development for a given target antigen depends on optimization of antibody selection, linker stability, cytotoxic drug potency, and mode of linker-drug conjugation to the antibody. Here, we systematically examined the in vitro potency as well as in vivo preclinical efficacy and saf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
213
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(224 citation statements)
references
References 24 publications
9
213
1
1
Order By: Relevance
“…These values returned to levels similar to control rats by day 14. Similar elevations in liver enzymes have been observed with thioTMAb-mpeo-DM1 (89 mg/kg or greater) and Trastuzumab-MCC-DM1 (20 mg/kg or greater) (15,30). Minimal hematologic changes included elevated neutrophils in rats treated with 60 or 90 mg/kg Her HC-A114pAF-NC-D1 on study day 5 (Table S4), similar to what has previously been observed with thioTMAbmpeo-DM1 (30).…”
Section: Nonnative Amino Acid Conjugates Demonstrate Superior In Vivosupporting
confidence: 83%
See 2 more Smart Citations
“…These values returned to levels similar to control rats by day 14. Similar elevations in liver enzymes have been observed with thioTMAb-mpeo-DM1 (89 mg/kg or greater) and Trastuzumab-MCC-DM1 (20 mg/kg or greater) (15,30). Minimal hematologic changes included elevated neutrophils in rats treated with 60 or 90 mg/kg Her HC-A114pAF-NC-D1 on study day 5 (Table S4), similar to what has previously been observed with thioTMAbmpeo-DM1 (30).…”
Section: Nonnative Amino Acid Conjugates Demonstrate Superior In Vivosupporting
confidence: 83%
“…Test article-related findings in the lungs included dosedependent congestion, alveolar edema, and increased alveolar macrophages. Similar findings were observed in rats treated with thioTMAb-mpeo-DM1 (30). Additional findings in rats treated with 60 or 90 mg/kg of Her HC-A114pAF-NC-D1 included subacute inflammation in the thymus and decreased lymphocytes in the thymus and spleen.…”
Section: Nonnative Amino Acid Conjugates Demonstrate Superior In Vivosupporting
confidence: 80%
See 1 more Smart Citation
“…The present effort aims to test a pretargeted approach in a clinically relevant model that features an internalizing target. 49 Not only has HER2 been exploited as a signaling target via the therapeutic antibody trastuzumab, 50 it has been further utilized as a drug delivery vector in the antibody-drug conjugate trastuzumab emtansine 51 and in clinical imaging of HER2-positive breast cancer. 4043 It should be noted, however, that HER2 is a somewhat unusual internalizing oncology target in that it exhibits extremely high expression levels and that trastuzumab binding does not down-regulate surface HER2, but instead passively recycles after HER2 endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Then all samples were washed using FACS buffer, followed by FACS analysis using a BD FACSCalibur system (BD Biosciences). 46 …”
Section: Egfr Binding Measurements By Elisa and Flow Cytometrymentioning
confidence: 99%